Psychometric properties of the Japanese version of the Occupational Fatigue Exhaustion Recovery Scale among shift‐work nurses. Issue 1 (3rd May 2022) - Yamaguchi, Shinya; Sato, Miho; Sumi, Naomi; Ito, Yoichi M.; Winwood, Peter C.; Yano, Rika
Abstract: Objectives: Shift‐work nurses are at a higher risk of inadequate recovery from fatigue and developing maladaptive fatigue with significant health consequences. Therefore, it is necessary to monitor fatigue and recovery levels with a reliable scale. We investigated psychometric properties of the Japanese version of the Occupational Fatigue Exhaustion Recovery scale (OFER‐J) for shift‐work nurses. Methods: Japanese shift‐work nurses responded to self‐administered questionnaires at baseline ( n = 942) and one month later ( n = 334). The confirmatory factor analysis (CFA) and exploratory factor analysis (EFA) were conducted to verify the structural validity and the correlation analysis and one‐way analysis of variance were conducted to test the construct and discriminative validity. Cronbach's alpha coefficient, intra‐class correlation coefficient (ICC), and smallest detectable change (SDC) were calculated to assess reliability. Results: The CFA showed high correlations between the factors and whilst the goodness‐of‐fit of the three‐factor model was suboptimal, it was in an acceptable range. Most modifications included the error covariance of the Acute Fatigue (AF) and Intershift Recovery (IR) items. The EFA showed that Chronic Fatigue (CF) and AF were not clearly separated, indicating that the two AF items dropped out. Construct and discriminative validity were also well indicated. Cronbach's alpha coefficients were 0.75–0.85. Only CF showed sufficient reproductivity (ICC = 0.74). The SDC for CF, AF, and IR was 14.0, 17.1, and 18.7, respectively. Conclusions: The validity and reliability of the OFER‐J were verified as acceptable for shift‐work nurses. The OFER‐J could contribute to a data‐based approach to fatigue management in nursing management practice.